Doxastic Arrogance Paradox - Wiśniewski, Andrzej (Logic and Logical Philosophy, 2025)
The Doxastic Arrogance Paradox, DAP, states that the belief that a proposition is an item of knowledge implies that the proposition holds/is true. Some possible sources of DAP, different from the negative introspection principle for knowledge, are pointed out. The emplacement of DAP among related paradoxes of epistemic-doxastic logics is characterized. Finally, some profits of identification of sources of DAP for the philosophical analysis of knowledge and belief are pointed out.